(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This paper aims to identify and analyze the barriers to healthcare access among students in the tertiary institutions in Nigeria. By conducting a thorough literature review, we have identified various factors that hinder students from seeking and receiving adequate healthcare services. These barriers include financial constraints, lack of awareness about available healthcare options, cultural and societal stigmas, and inadequate healthcare infrastructure. We also explore the impact of these barriers on the health and well-being of the student population and suggest potential solutions to address them. The findings suggest that addressing these barriers is crucial for promoting the overall health of students and ensuring their academic success. This research highlights the need for policymakers and healthcare providers to prioritize the unique healthcare needs of students in tertiary institutions in Nigeria.